Modulation of Primary Immune Response by Different Vaccine Adjuvants - Ciabattini, Annalisa; Pettini, Elena; Fiorino, Fabio; Pastore, Gabiria; Andersen, Peter; Pozzi, Gianni; Medaglini, Donata (Frontiers in Immunology, 2016)
Adjuvants contribute to enhancing and shaping the vaccine immune response through different modes of action. Since the primary immune response can influence the overall quality of the response generated, here we investigate early biomarkers of adjuvanticity after primary immunization with four different adjuvants combined with the chimeric tuberculosis vaccine antigen H56. C57BL/6 mice were immunized by the subcutaneous route with different vaccine formulations, and the modulation of primary CD4+ T cell and B cell responses was assessed within draining lymph nodes, blood and spleen, 7 and 12 days after priming. Vaccine formulations containing the liposome system CAF01 or a squalene-based oil-in-water emulsion (o/w Squalene), but not aluminum hydroxide (Alum) or CpG ODN 1826, elicited a significant primary antigen-specific CD4+ T cell response compared to antigen alone, 7 days after immunization. The effector function of activated CD4+ T cells was skewed towards a Th1/Th17 response by CAF01, while a Th1/Th2 response was elicited by o/w Squalene. Differentiation of B cells in short-lived plasma cells, and subsequent early H56-specific IgG secretion, was observed in mice immunized with o/w Squalene or CpG adjuvants. Tested adjuvants promoted the germinal centre reaction with different magnitude. These results show that the immunological activity of different adjuvants can be characterized by profiling early immunization biomarkers after primary immunization. These data and this approach could give an important contribution to the rational development of heterologous prime-boost vaccine immunization protocols.